2021
DOI: 10.3390/su13147574
|View full text |Cite
|
Sign up to set email alerts
|

Linking the Determinants of Air Passenger Flows and Aviation Related Carbon Emissions: A European Study

Abstract: Increasing global concern regarding the negative consequences of climate change will see the introduction of comprehensive policy governing aviation-related carbon emissions. With demand for air travel set to accelerate over the next three decades airlines are faced with the task of catering to increased demand while simultaneously achieving emission reductions. In this study we identify the determinants of air passenger flows and flight frequency and assess their impact on carbon emissions and carbon efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…They pointed out that distance and aircraft size had a positive effect on CO 2 emissions from aviation. However, contrary to Yue and Byrne [5], and somewhat counterintuitively, Lo et al [6] found that fuel price and CO 2 emissions were positively correlated.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…They pointed out that distance and aircraft size had a positive effect on CO 2 emissions from aviation. However, contrary to Yue and Byrne [5], and somewhat counterintuitively, Lo et al [6] found that fuel price and CO 2 emissions were positively correlated.…”
Section: Introductionmentioning
confidence: 85%
“…Williams and Noland [4] demonstrated that long-distance flights offered lower CO 2 per km rates than shorter ones. Yue and Byrne [5] analyzed various factors affecting airline carbon emissions in European aviation. They indicated that CO 2 emissions were positively correlated with the number of passengers and flights.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy must be pursued vigorously, ensuring that the pace of development within the sector remains unaffected. The dual objectives of sustaining growth while significantly lowering emission intensity present a nuanced challenge, underscoring the necessity for innovative approaches in technological, operational, and policy frameworks that support sustainable aviation practices [6].…”
Section: Introductionmentioning
confidence: 99%
“…Air transportation is one of the agents and drivers of economic development whose demand is expected to accelerate in the next three decades (Yue & Byrne, 2021). In addition, air transport is an indicator of development as its volume clearly depends on the level of economic activity as well as on the prosperity of the population (Bourguignon & Darpeix, 2016).…”
Section: Introductionmentioning
confidence: 99%